Propionate and Butyrate Produced by Gut Microbiota after Probiotic Supplementation Attenuate Lung Metastasis of Melanoma Cells in Mice. Issue 15 (18th June 2021) - Chen, Lili; Zhou, Xinyu; Wang, Yawei; Wang, Dake; Ke, Yueshuang; Zeng, Xianlu
Abstract : Scope: The beneficial effects of probiotics in reducing gastrointestinal inflammation and in preventing colorectal cancer have been reported, but the mechanism underlying the immunomodulatory effect of probiotics in inhibiting extra‐intestinal tumor progression remains unclear. Methods and Results: This study shows that probiotic supplementation attenuate lung metastasis of melanoma cells in mice. Feeding mice with VSL#3 probiotics change the composition and proportion of gut microbiota. The changes in gut bacteria composition, such as in the abundance of Lachnospiraceae, Streptococcus, and Lachnoclostridium, are associated with the production of short‐chain fatty acids in the gut. The concentrations of propionate and butyrate are upregulated in gut and blood after feeding VSL#3, and the increase in propionate and butyrate levels promotes the expression of chemokine (C‐C motif) ligand 20 (CCL20) in lung endothelial cells and the recruitment of T helper 17 (Th17) cells to the lungs via the CCL20/chemokine receptor 6 axis. The recruitment of Th17 cells decreases the number of tumor foci in lungs and attenuates the lung metastasis of melanoma cells in mice. Conclusions: The results provide new information on the role and mechanisms of action of probiotics in attenuating extra‐intestinal tumor metastasis. Abstract : Feeding mice with VSL#3 increases the number of SCFAs‐producing bacteria in the gut. An increase in propionate and butyrate promotes the expression of CCL20 in lung endothelial cells and the recruitment of Th17 cells to the lungs via CCL20/CCR6 axis. The recruitment of Th17 cells attenuate the lung metastasis of melanoma cells in mice.